Technical Note: Dose effects of 1.5 T transverse magnetic field on tissue interfaces in MRI‐guided radiotherapy. Issue 8 (26th July 2016) - Chen, Xinfeng; Prior, Phil; Chen, Guang‐Pei; Schultz, Christopher J.; Li, X. Allen
Abstract : Purpose: The integration of MRI with a linear accelerator (MR‐linac) offers great potential for high‐precision delivery of radiation therapy (RT). However, the electron deflection resulting from the presence of a transverse magnetic field (TMF) can affect the dose distribution, particularly the electron return effect (ERE) at tissue interfaces. The purpose of the study is to investigate the dose effects of ERE at air‐tissue and lung‐tissue interfaces during intensity‐modulated radiation therapy (IMRT) planning. Methods: IMRT and volumetric modulated arc therapy (VMAT) plans for representative pancreas, lung, breast, and head and neck (HN) cases were generated following commonly used clinical dose volume (DV) criteria. In each case, three types of plans were generated: (1) the original plan generated without a TMF; (2) the reconstructed plan generated by recalculating the original plan with the presence of a TMF of 1.5 T (no optimization); and (3) the optimized plan generated by a full optimization with TMF = 1.5 T. These plans were compared using a variety of DV parameters, including V 100%, D 95%, DHI [dose heterogeneity index: ( D 20% – D 80% )/ D prescription ], D max, and D 1cc in OARs (organs at risk) and tissue interface. All the optimizations and calculations in this work were performed on static data. Results: The dose recalculation under TMF showed the presence of the 1.5 T TMF can slightly reduce V 100% and D 95% for PTV, with the differences being less than 4% for all but one lung case studied. The TMF results in considerable increases in D max and D 1cc on the skin in all cases, mostly between 10% and 35%. The changes in D max and D 1cc on air cavity walls are dependent upon site, geometry, and size, with changes ranging up to 15%. The VMAT plans lead to much smaller dose effects from ERE compared to fixed‐beam IMRT in pancreas case. When the TMF is considered in the plan optimization, the dose effects of the TMF at tissue interfaces (e.g., air‐cavity wall, lung‐tissue interfaces, skin) are significantly reduced in most cases. Conclusions: The doses on tissue interfaces can be significantly changed by the presence of a TMF during MR‐guided RT when the magnetic field is not included in plan optimization. These changes can be substantially reduced or even eliminated during VMAT/IMRT optimization that specifically considers the TMF, without deteriorating overall plan quality.